INNOVATIVE PROVISION STATE ANALYSIS OF THE ENTREPRENEURSHIP DEVELOPMENT IN RURAL AREA OF UKRAINE - PYSKLYVETS, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Innovative support for rural entrepreneurship in Ukraine is of particular importance in the context of the country’s European integration course and the need to modernize the agricultural sector. However, the current state of innovative activity in rural areas is characterized by a number of problems that slow down the dynamics of entrepreneurship development. The main purpose of this publication is to analyze the state of innovative support for the development of entrepreneurship in rural areas of Ukraine. An analysis of operating business entities registered in Ukraine for 2014-2023 was carried out. Separately, an analysis of operating business entities engaged in agriculture for 2014-2023 was carried out. A detailed analysis of capital investments by type of assets by type of economic activity for 2021-23 was carried out. The dynamics of changes in the share of capital investments in intangible assets in the production of food products, beverages and tobacco products in the total volume of capital investments of the corresponding type of economic activity in accordance with the indicators of sustainable development goals was determined. The Rating of Ukraine in the Global Innovation Index for 2020-2024 has been summarized. The indicator share of capital investments in intangible assets in the production of food, beverages and tobacco products in the total volume of capital investments in the corresponding type of economic activity, percent (SDG indicator 2.2.3) has been analyzed, which corresponds to task 2 (increasing the level of agricultural productivity), goal 2 (overcoming hunger, developing agriculture). The main problematic issues of innovative support for the development of entrepreneurship in rural areas have been outlined. The main directions for achieving sustainable growth of innovations in agricultural entrepreneurship have been identified.